Validation of baking as a kill-step for controlling Shiga toxin-producing Escherichia coli during traditional crust pizza baking process - Singh, Arshdeep; Channaiah, Lakshmikantha H. (Frontiers in Microbiology, 2022)
A study was conducted to validate a simulated traditional crust pepperoni pizza baking process to control Shiga toxin-producing E. coli (STEC) and to determine the heat resistance characteristics of STEC in pizza dough. Pizza dough and pepperoni slices were inoculated with 7 strains STEC cocktail and baked at 500 °F (260°C) for 12 minutes using a conventional kitchen oven followed by 15 minutes of ambient air cooling. The mean internal temperature of the pizza reached 209.32 ± 1.94 °F by the end of 12 minutes of baking and dropped to 137.90 ± 2.88 °F after the 15 minutes ambient air cooling. The aw and pH of the traditional crust pizza did not alter significantly during the baking process. The STEC population decreased by >5 log CFU/g in traditional crust pizza after 12 minutes of baking. Where pepperoni slices were used as a source of STEC introduction, a reduction of > 6.5 log CFU/g was observed. The D-values of STEC cocktail in pizza dough at 55, 58, 61°C were 49.5 ± 4.10, 15.3 ± 0.68, and 2.8 ± 0.31 min, respectively. The z-value of STEC was 4.8 ± 0.16 °C. This study validated that a typical traditional crust pizza baking process with ~209°F internal temperature for at least 12 minutes will result in 5 log reductions in STEC population.